Pengaruh Gaya Kepemimpinan dan Motivasi terhadap Kinerja Karyawan pada Industri UMKM di Wilayah D.I. Yogyakarta - Bambang Irjanto; Herman Setiawan (Universitas Proklamasi 45 Yogyakarta, 2016)
Micro, small, and medium enterprises (SMEs) have an important role in the development of Indonesia's economy. They became a great power when Indonesia faced economic crisis. In addition to contributing to the national income, SMEs also have a role in providing jobs. In the face of the free market, SMEs must be able to keep up with increasing business productivity. This will happen if the quality of employee performance is good. Quality performance or achievements of good work is often influenced by several factors, could be influenced by his friend can also be influenced by his superiors. A boss usually has a leadership style that aims to influence the performance of subordinates in the hope of achieving organizational goals. In addition to leadership style, things that can affect performance is motivation. With the motivation, employees will be encouraged to work well, so they will show good performance quality performance as well. The objective of this study was to examine the effect of leadership style and motivation on employee performance in industrial SMEs in the Special Region of Yogyakarta (DIY). This study uses survey the population of all employees of the company are classified as micro, small, and medium in DIY. The sampling method used is sampling by convenience non-probability sampling. In this study, 100 samples were taken. Methods of data collection is done by using a questionnaire containing several questions with methods of data analysis using multiple regression.The results of this study is to accept the second hypothesis proposed in which leadership style has positive influence on employee performance in industrial SMEs in DIY. And, motivation positive influence on employee performance in industrial SMEs in DIY.